ANALISIS FAKTOR-FAKTOR PENENTU KUALITAS AUDIT DENGAN MORAL JUDGMENT SEBAGAI PEMODERASI (STUDI PADA BPK RI PERWAKILAN PROVINSI MALUKU UTARA) - Mahdi, Suriana AR. (JURNAL AKUNTANSI DAN AUDITING, 2014)
This study generally aims to analyze determinants audit quality with moral judgment as themoderating and has a specific purpose to know; influence of competence on perceived audit quality,the influence of independence on perceived audit quality, the influence of due professional care onperceived audit quality, the influence of leadership style on perceived audit quality, the influenceof organizational culture on perceived audit quality, the influence of moral judgment on perceivedaudit quality and partially, competence, independence, due professional care, leadership style andorganizational culture influence of perceived audit quality with moral judgment as a moderatingvariable. This study is an empirical study using saturation sampling technique. Data obtained bydistributing questionnaires to 44 auditors BPK RI representatives of North Maluku province, withresponse rate as much 86.4%. Data analysis was performed using regression analysis or test theassumption of Ordinary Least Square (OLS) with a regression test to test the absolute differencevalue on variable moderation. These results indicate that: Auditor competence may increase theperceived audit quality, auditor independence may increases perceived audit quality, auditor dueprofessional may attitude may increases perceived audit quality, leadership style may increasesperceived audit quality, organizational culture had no effect on perceived auditor quality andmoral judgment does not strengthen or weakens perceived audit quality, but a moral judgment onan individual basis may increases perceived audit quality.